2016
DOI: 10.7120/09627286.25.3.365
|View full text |Cite
|
Sign up to set email alerts
|

The stunning and slaughter of cattle within the EU: a review of the current situation with regard to the halal market

Abstract: The slaughter of animals for the Halal market is both ethically and economically significant. There are animal welfare and spiritual requirements that must be met for meat to be considered fit for Muslim consumption. These requirements are enshrined in Islamic law, known commonly as the Shariah law, derived from commandments in the Holy Quran and the Hadith (teachings or traditions of the Prophet of Islam, Mohammed-Peace Be Upon Him). Islamic jurists widely interpret the Shariah law differently, and this has l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 43 publications
(16 reference statements)
0
50
0
Order By: Relevance
“…With guidance from the Quran and Hadith, one would expect these jurists to make unanimous decisions regarding what is Halal and Haram (prohibited), however, a number of differences of opinion exist among the scholars. Fuseini, et al, (2016a) suggested that the differences in scholarly opinion may sometimes be the result of differences between the two main sects, Sunni and Shia or the subdivision of the Sunni sect into four different schools of law; the Maliki, Hanbali, Shafii and Hanafi schools of law.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With guidance from the Quran and Hadith, one would expect these jurists to make unanimous decisions regarding what is Halal and Haram (prohibited), however, a number of differences of opinion exist among the scholars. Fuseini, et al, (2016a) suggested that the differences in scholarly opinion may sometimes be the result of differences between the two main sects, Sunni and Shia or the subdivision of the Sunni sect into four different schools of law; the Maliki, Hanbali, Shafii and Hanafi schools of law.…”
Section: Discussionmentioning
confidence: 99%
“…Animals slaughtered for Muslim consumption must meet specific requirements laid down in the Islamic Holy Book, the Quran, and the teachings of the Prophet contained in the various Ahadith (Grandin and Regenstein, 1994, Regenstein, Chaudry & Regenstein, 2003, Nakyinsige et al, 2013, Fuseini, Knowles, Lines, Hadley, & Wotton, 2016a. These Islamic dietary laws prohibit the consumption of meat (and by-products) from carnivorous animals, pigs, animals that die naturally and all forms of intoxicants (MS1500, 2009, HFA, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The Quran and Hadith are the two main sources of Islamic food laws (Grandin and Regenstein 1994;Fuseini et al 2016a), giving guidance on the production, handling and slaughter of animals for food. A number of verses in the Quran lay emphasis on the Halal-Tayyib concept (Quran: 2:168;5:88;8:69).…”
Section: The Halal-tayyib Conceptmentioning
confidence: 99%
“…This is because in many Muslim-minority countries, the majority of processed foods may contain non-Halal raw materials (e.g. pork or porcine derivatives) and the processing of Halal products may be done using equipment that are also used to process pork-based products [4], this leads to the contamination of Halal food. In addition, non-Muslims generally perform the slaughter of animals for human consumption in Muslim-minority countries, such meats are therefore not recognised as suitable for Muslim consumption by some Muslim authorities.…”
Section: Introductionmentioning
confidence: 99%